Gastrointestinal and external parasitism in the Magellanic Horned Owl Bubo magellanicus (Strigiformes: Strigidae) in Chile - Grandón-Ojeda,Alexandra (2018)
Abstract To describe the parasitic community of the Magellanic Horned Owl, Bubo magellanicus (Aves, Strigiformes), 19 carcasses from central Chile were analyzed. Ectoparasites were collected through plumage inspection, while endoparasites were collected through traditional techniques of parasitological necropsy. Sixteen owls were infected with at least one species of ectoparasite (84.21%) or endoparasite (31.58%). Eleven of 19 birds (57.89%) harbored feather mites of the three species Pandalura cirrata (42.11%), Glaucalges attenuatus (47.37%), and Kramerella sp. (10.53%), whereas 16 individuals (84.21%) harbored the chewing louse Strigiphilus chilensis. Only six birds (31.58%) were infected with helminths; the nematodes Capillaria tenuissima (26.32%) and Dispharynx nasuta (5.26%); the acanthocephalan Centrorhynchus spinosus (5.26%); and the trematode Neodiplostomum sp. (5.26%). Apart from S . chilensis, all parasites comprised new records for B . magellanicus.